2020
DOI: 10.1021/acs.organomet.0c00258
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal-to-Single-Crystal [2 + 2] Photodimerization Involving B←N Coordination with Generation of a Thiophene Host

Abstract: We report on B←N coordination to support a single-crystal-to-single-crystal reaction in the solid state. A [2 + 2] photodimerization is achieved with face-to-face π-stacks of monotopic B←N adducts composed of a phenylboronic acid catechol ester and an alkene with a terminal thiophene group. The photoreaction generates a ditopic B-adduct involving a head-to-tail cyclobutane regio- and stereoselectively. The photodimerization is accompanied by an increase in the tetrahedral character of the B atom. The resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Generality of the approach using the B←N interaction of boronic esters to achieve [2+2]-photocycloadditions was evaluated with thiophene trans-1-(4-pyridyl)-2-(2-thienyl)ethylene (pte). 34 [2+2]-Photodimerizations of thiophenes are extremely rare both in solution and in the solid state despite being desirable for the fields of electronics and organic semiconductors. 35 The template approach to perform [2+2]-photodimerizations involved B←N coordination of pte with be to afford a T-shaped monoboron adduct (be)•(pte).…”
Section: Crystal Reactivity Of B←n-bonded Adducts: the Case Of Styrylthiophenesmentioning
confidence: 99%
“…Generality of the approach using the B←N interaction of boronic esters to achieve [2+2]-photocycloadditions was evaluated with thiophene trans-1-(4-pyridyl)-2-(2-thienyl)ethylene (pte). 34 [2+2]-Photodimerizations of thiophenes are extremely rare both in solution and in the solid state despite being desirable for the fields of electronics and organic semiconductors. 35 The template approach to perform [2+2]-photodimerizations involved B←N coordination of pte with be to afford a T-shaped monoboron adduct (be)•(pte).…”
Section: Crystal Reactivity Of B←n-bonded Adducts: the Case Of Styrylthiophenesmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) and coordination polymers (CPs) are very attractive because of their designability and/or tunability in both crystalline structure and functionality, which offer an opportunity for developing advanced functional materials. , Structural transformations, especially single-crystal to single-crystal (SCSC) transformations, in these polymeric materials are attractive because they usually occur cooperatively with interesting phenomena that might promote and/or introduce exotic functionalities into the materials. These particular properties could be triggered by various stimulators such as light, solvent, guest sorption–desorption, and even chemical reactions. The SCSC transformation in coordination compounds, in some cases, causes a conversion of the metal coordination geometry that leads to a change in material properties such as optical properties, as well as catalytic activity. Along with the exponential increase in the number of reported MOFs, various synthetic methods have been intensely explored in order to reduce the consumption of time and energy as well as minimize chemical waste. , Among the rapid and green synthetic routes to porous MOFs, the microwave-assisted technique has become one of the promising alternative ways that can facilitate the repeatable and controllable productions of these functional materials within a few minutes. On the other hand, among the numbers of MOFs that exhibit semiconduction, the well-known Zn-MOF [Zn 4 O­(BDC) 6 ] or MOF-5, with a band gap energy of 3.4–4.0 eV, showed photocatalytic activity upon phenol degradation . Apart from ZnO semiconductors as photocatalysts, the potential application of Zn-MOFs in photocatalysis has become more attractive. , In addition, SCSC transformation studies involving both ligand substitution and time have rarely been reported and may reveal a greater understanding of the kinetics of the transformation .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the asymmetric azo chromophore 4-phenylazopyridine ( 4PAzP ) coordinates orthogonally to tris­(pentafluorophenyl)­borane ( BCF ) to achieve the formation of a tripod-shaped boron adduct ( BCF )·( 4PAzP ) (Scheme a,b). The adduct ( BCF )·( 4PAzP ) self-assembles into molecular helices (Scheme c) sustained by a combination of perfluorophenyl embraces , and boron coordination in the crystalline solid state where the molecular transition dipole moment from the chromophore is oriented in parallel and therefore generates dichroic behavior (Scheme d–f). To the best of our knowledge, there are no documented examples of dichroism enhancement of an asymmetric azo chromophore (i.e., 4PAzP ) and the application of perfluorophenyl embraces and/or boron coordination to achieve dichroism.…”
mentioning
confidence: 97%
“…Single-crystal X-ray diffraction analysis (Tables S1 and S2 BCF undergoes a change in geometry from trigonal planar 39 to tetrahedral. 31,33,40 The B ← N bonds are slightly weaker compared to similar adducts, 31,32,34 as evidenced by the tetrahedral characters (THC) 41 crystal of (BCF)•(4PAzP) (100 face) were recorded every 10°o f rotation using a rotating stage (Figure 3b, Video S2, Supporting Information). A polar plot of the transmittance of the red, green, and blue (RGB) intensities observed under POM confirmed the anisotropic behavior in single crystals of (BCF)•(4PAzP) with respect to the plane of polarized light (Figure 3c).…”
mentioning
confidence: 99%
See 1 more Smart Citation